Interaksi total quality management dan sistem reward terhadap kinerja manajerial pada BPR di Kabupaten Banyumas - Tjahjani Murdijaningsih; Heru Cahyo; Heri Setiawan; Arinastuti Arinastuti (Faculty of Economics and Business Universitas Jenderal Soedirman, 2017)
Background: This research entitled “Interaction of total quality management and reward system on managerial performance at BPR in Banyumas Regency”. Purpose: This study aims to determine whether the interaction between total quality management and reward system can significantly affect the managerial performance. Methodology: The sample of this study was the managers both top managers and lower managers who have control over some subordinates. Findings: The result shows that total quality management has a significant effect on managerial performance as well as total quality management after interacting with reward system can also affect managerial performance, so if the company will improve the performance of its managerial must pay attention to total quality management by aligning a good reward system. Keywords: total quality management, reward system, managerial performance.